Efforts to Prevent and Handle Sexual Violence in Higher Education - Farida, Anis; Handoko, Priyo (Magister Hukum Tata Negara Pascasarjana UIN Sunan Ampel Surabaya, 2024)
This research explains various efforts to prevent and overcome sexual violence in higher education. This research uses normative research methods with a legislative and historical approach and analyzes the problems raised by legal protection theory and legal theory as a social engineering tool. The Chancellor of UIN Sunan Ampel formed a Task Force for the Prevention and Control of Sexual Violence. The Task Force Team is tasked with outreach to work units within the UIN Sunan Ampel environment. The outreach is carried out by holding lectures via Zoom meetings or face-to-face and by making short educational videos about efforts to prevent and handle sexual violence. In addition, it also provides a hotline channel to report acts of sexual violence, providing a space to receive direct reports from victims and assistants them. This effort aligns with the promulgation of Law Number 12 of 2022 concerning Crimes of Sexual Violence. From a progressive legal perspective, legislation is expected to encourage social change in society, especially the environment, in terms of preventing and dealing with sexual violence in higher education environments to create safe university institutions free from sexual violence.